Perfil epidemiológico e análise espacial da hanseníase na área de atuação da Estratégia Saúde da Família. Belém - Pará - LIMA, Kaio Pantoja de (2019)
Leprosy is a chronic infectious contagious disease, endemic in Brazil, and constitutes a serious public health problem in many countries. For this reason, it is necessary to intensify the epidemiological surveillance actions, aimed at greater effectiveness in the diagnosis and treatment of the disease, especially, identifying areas of greater concentration of cases, through Geographic Information Systems. Objective: To describe the epidemiological profile, the spatial distribution of leprosy cases and the service quality of the Family Health Strategy of the Parque Amazônia I, in Belém, from 2008 to 2015. Method: quantitative study, with a descriptive and transversal study design . Research scenario: area of activity of the Family Health Strategy Parque Amazônia I, neighborhood: Terra Firme, Guamá Administrative District, Belém, Pará, Brazil. Study population: cases of leprosy reported by the Family Health Strategy of the Parque Amazônia I, from 2008 to 2015. Results: a result of 14 patients with leprosy was reported, with a higher frequency of male patients (71.43% ), In relation to the female (28.57%). The predominant skin color was brown (42.86%), followed by black patients (35.71%) and white patients (21.43%). More than half of the reported cases corresponded to patients with incomplete primary education (57.14%). The age group of the highest proportion found age between 20 and 39 years (43%), corresponding to the economically active population. The most frequently found "occupation" was students (21.44%). There was a predominance of the multibacillary form among the cases reported in the study period. Cases with physical disability I and II were observed in the year 2015. The highest detection rates per 1000 inhabitants were obtained during the execution of an Extension Project financed by the Ministry of Health. The method of detection of new cases More frequent was by spontaneous demand (42.86%), followed by cases via referral (28.57%). Of the reported cases, 42.86% were located outside the assigned area, and 35.71% were located near the unit. The quality of the actions and services provided by the Health Strategy of the Family Park Amazonia I oscillated between Good and Precarious, regarding the examination of intradomiciliary contacts. Conclusion: epidemiological profile and the use of spatial analysis techniques may influence better planning and organization of the activities carried out by the health team of the Family Health Strategy Parque Amazônia I.